KEPUTUSAN PEMBELIAN ULANG KONSUMEN PADA RUMAH MAKAN RAJA SATE DAN SOTO SERTA FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Abdullah; Reza Widhar Pahlevi; Narwanto Nurcahyo (Bajang Institute, 2022)
This study aims to determine the consumer repurchase decisions of Raja and Soto restaurants in Yogyakarta. Through the questionnaire method, the sample in this study amounted to 139 respondents who were consumers of the Raja Sate and Soto Restaurants in Yogyakarta. The data analysis technique used multiple linear regression analysis with the SPSS program. Based on the results of multiple linear regression, it was found that 0.5555> 0.05 location had no significant effect on consumer repurchase decisions at Raja Sate and Soto restaurants. and Soto. It was found that 0.000 < 0.05 price had a significant effect on consumers' repurchase decisions at Raja Sate and Soto restaurants. The results found that 0.001 < 0.05 service quality had a significant effect on consumer repurchase decisions at Raja Sate and Soto restaurants.